2016
DOI: 10.1111/apa.13472
|View full text |Cite
|
Sign up to set email alerts
|

Children with developmental dyslexia showed greater sleep disturbances than controls, including problems initiating and maintaining sleep

Abstract: Results: Compared to the controls, the children with DD showed significantly higher rates of above threshold scores on the total SDSC score (p<0.001) and on the subscales for disorders in initiating and maintaining sleep (p<0.001), sleep breathing disorders (p<0.001) and disorders of arousal (p<0.001).. Conclusion:Sleep disorders were significantly more frequent in children with DD than in healthy controls. A possible relationship between dyslexia and sleep disorders may have relevant clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…In fact, affected children and adolescents present specific cognitive impairments (Posar et al, 2014), which pinpoint the close relationship between sleep and cognition (Esposito and Carotenuto, 2014). Moreover, probably due to the same role in sleep modulation, orexin seems to be also involved in the pathogenesis of migraine (Rainero et al, 2008) as suggested by the link between NREM sleep instability and risk of cognitive impairments and behavioral problems (McCoy and Strecker, 2011; Bruni et al, 2012; Colonna et al, 2015; Carotenuto et al, 2016, Figure 3). …”
Section: Sleep/wake Regulationmentioning
confidence: 96%
“…In fact, affected children and adolescents present specific cognitive impairments (Posar et al, 2014), which pinpoint the close relationship between sleep and cognition (Esposito and Carotenuto, 2014). Moreover, probably due to the same role in sleep modulation, orexin seems to be also involved in the pathogenesis of migraine (Rainero et al, 2008) as suggested by the link between NREM sleep instability and risk of cognitive impairments and behavioral problems (McCoy and Strecker, 2011; Bruni et al, 2012; Colonna et al, 2015; Carotenuto et al, 2016, Figure 3). …”
Section: Sleep/wake Regulationmentioning
confidence: 96%
“…However, the association of dyslexia with insomnia is not much reported and less understood. A study by Carotenuto et al showed an increased prevalence of sleep disorders in dyslexia [2]. This is attributed to the increase in number of sleep spindles and long periods of slow wave sleep which reflects on language learning [12].…”
Section: Discussionmentioning
confidence: 99%
“…Learning and cognitive skills of children depend on good quality of sleep. Sleep disorders were found to have a higher prevalence in children with dyslexia [2]. We report a rare case of psychophysiological insomnia diagnosed in a nine-year-old boy, the evaluation of which unmasked his learning disability.…”
Section: Introductionmentioning
confidence: 84%
“…Some of these may be causal to varying degrees (Table ). The common associated problems include ADHD, anxiety and poor mental health, motor co‐ordination and sleep problems . It may be necessary to address complicating problems (such as sleep, ADHD or mental health) before the learning problems can be managed appropriately. Immediate management: Before remediation (activities intended to accelerate learning in the affected area), several preliminary steps provide a foundation for ongoing success: ○ Common understanding: Consider the set of people involved in the child's care (parents, teachers, tutors, relatives) and ensure a communication strategy that enables them all to understand the child's SLD in the same way.…”
Section: What the Doctor Can Domentioning
confidence: 99%